Pregunta
upstudy study bank question image url

\( x ^ { \frac { 4 } { 3 } } - \sqrt[ 3 ] { x ^ { 2 } } - 72 = 0 \)

Ask by Lyons Murray. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions are \( x = 27 \) and \( x = -27 \).

Solución

To solve the equation: \[ x^{\frac{4}{3}} - \sqrt[3]{x^2} - 72 = 0 \] **Step 1: Substitute** Let’s make a substitution to simplify the equation. Let: \[ y = x^{\frac{1}{3}} \] Then: \[ x = y^3 \] Now, express the original equation in terms of \( y \): \[ (x^{\frac{4}{3}}) = (y^3)^{\frac{4}{3}} = y^4 \] \[ (\sqrt[3]{x^2}) = (y^3)^{\frac{2}{3}} = y^2 \] Substituting these into the equation: \[ y^4 - y^2 - 72 = 0 \] **Step 2: Solve the Quartic Equation** Let’s set \( t = y^2 \). The equation becomes: \[ t^2 - t - 72 = 0 \] Solve for \( t \) using the quadratic formula: \[ t = \frac{1 \pm \sqrt{1 + 288}}{2} = \frac{1 \pm \sqrt{289}}{2} = \frac{1 \pm 17}{2} \] This gives: \[ t = 9 \quad \text{or} \quad t = -8 \] Since \( t = y^2 \) and \( y^2 \) cannot be negative: \[ t = 9 \implies y^2 = 9 \implies y = \pm 3 \] **Step 3: Back-Substitute to Find \( x \)** Recall that: \[ y = x^{\frac{1}{3}} \implies x = y^3 \] Thus: 1. If \( y = 3 \): \[ x = 3^3 = 27 \] 2. If \( y = -3 \): \[ x = (-3)^3 = -27 \] **Step 4: Verify Solutions** Plugging back into the original equation: - For \( x = 27 \): \[ 27^{\frac{4}{3}} - \sqrt[3]{27^2} - 72 = 81 - 9 - 72 = 0 \] - For \( x = -27 \): \[ (-27)^{\frac{4}{3}} - \sqrt[3]{(-27)^2} - 72 = 81 - 9 - 72 = 0 \] Both solutions satisfy the original equation. **Final Answer:** The real solutions are \( x = 27 \) and \( x = -27 \).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( x^{\frac{4}{3}} - \sqrt[3]{x^2} - 72 = 0 \), let's first make a substitution to simplify the expression. Let \( y = \sqrt[3]{x} \). Then, we can rewrite the equation as: \( y^{4} - y^{2} - 72 = 0 \). This is a quadratic in terms of \( y^{2} \). Let \( z = y^{2} \), transforming the equation into: \( z^{2} - z - 72 = 0 \). Now, we apply the quadratic formula: \[ z = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{1 \pm \sqrt{1 + 4 \cdot 72}}{2} = \frac{1 \pm \sqrt{289}}{2} = \frac{1 \pm 17}{2}. \] This results in \( z = 9 \) or \( z = -8 \). Since \( z = y^{2} \), it must be non-negative, so we discard \( z = -8 \) and take \( z = 9 \). Now, we have: \[ y^{2} = 9 \implies y = 3 \text{ or } y = -3. \] Recalling our substitution \( y = \sqrt[3]{x} \): 1. \( \sqrt[3]{x} = 3 \implies x = 27 \). 2. \( \sqrt[3]{x} = -3 \implies x = -27 \). Thus, the solutions to the original equation are: \[ \boxed{27 \text{ and } -27}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad